Manager - Required Skills and Attributes in Effective Management of a Company - Piasecka-Głuszak, Agnieszka (Menedżer - wymagane umiejętności i cechy w skutecznym zarządzaniu przedsiębiorstwem, 2010)
Manager is a person occupying a managerial position at different levels in a company hierarchy, who participates in the implementation of basic functions of the company, such as planning, organizing, leading, motivating and controlling as well. This is a person with broad knowledge and skills in the management of organization resources. Taking many decisions, on one hand may contribute to the development, growth of the company but on the other it may lead to weakness or even to company fall. This article aims to give some insight into manager position, a person who is able to manage enterprise resources effectively and efficiently. The author presents among others a definition and types of manager, his basic characteristics, required skills and tasks performed by him.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 136, s. 127-137
Keywords: manager; manager in the enterprise; manager's skills; manager's characteristics; contemporary manager